2014
DOI: 10.1007/s40626-014-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic capacity, growth and water relations in ‘Golden’ papaya cultivated in vitro with modifications in light quality, sucrose concentration and ventilation

Abstract: This study assessed the ecophysiological aspects of the in vitro multiplication of 'Golden' papaya in response to different light qualities, ventilation systems and sucrose concentrations related to photosynthesis, chlorophyll fluorescence, water balance and growth. The treatments were performed in a complete, randomised split-plot design with four replicates. These treatments consisted of white and red light, closed and ventilated culture systems and four sucrose concentrations (10, 20, 30 and 40 g L -1 ) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…by changing the osmotic balance. There are even references about sucrose toxicity in high dosages for certain plants (Schmildt et al ). Thus, the question arises, why not just remove or reduce the sucrose supply during in vitro cultivation?…”
Section: Discussionmentioning
confidence: 99%
“…by changing the osmotic balance. There are even references about sucrose toxicity in high dosages for certain plants (Schmildt et al ). Thus, the question arises, why not just remove or reduce the sucrose supply during in vitro cultivation?…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to those of previous studies; the root fresh mass and dry mass of triticale decreased under salt stress, the pretreatment with glucose and sucrose could maintain or enhance these traits, and the pretreatment with mannitol did not relieve the reductions of root fresh mass and dry mass. Schmildt et al (2015) found that the increased production of papaya dry biomass was caused by the application of an exogenous carbon source. Campostrini et al (2008) also found that shoot dry matter was increased by sucrose in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies carried out on other species, subjected to a 16 h photoperiod, low concentration of CO 2 into the vessels was observed: Pfaffia glomerata [ 246 ], Solanum tuberosum [ 247 , 248 ], Carica papaya [ 249 ], Castanea sativa [ 227 ], Vitis vinifera [ 250 , 251 ], Fragaria x ananassa [ 252 ], Hyptis marrubioides and Hancornia speciosa [ 253 ].…”
Section: Effects Of Photoperiodmentioning
confidence: 99%